Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Di Sekolah Minoritas Muslim Di SMP Negeri 26 Kabupaten Sorong Papua - Ayu Sadewi; M. Makhrus (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
How important education is today as a human need to be able to grow and develop along with the rapid development of the times. This includes Islamic religious education and character education which is very influential so that children can grow up with good spirituality. Islamic Religious Education and Character Education, especially in schools, are expected to be able to make children learn to respect, respect and love each other, including non-Muslims. In Indonesia itself, the problem of adequate education is not felt by all regions, including Papua. Papua is a Muslim minority area, but despite this, learning about Islamic Religion and Character has been implemented in schools, including at SMP Negeri 26, Sorong Regency, Papua. Therefore, the aim of this research was to find out how Islamic Religious Education learning at SMP Negeri 26 Sorong Regency, Papua was carried out. The research method that the author uses is qualitative using a phenomenological approach. The data collection techniques used were interviews and documentation. From this research it was found that there were 40% of female students who were Muslim at SMP Negeri 26, Sorong Regency, Papua. Even though it is a school with Muslim minority students, the sense of tolerance and mutual respect between people of different religions is very high. The implementation of Islamic Religious Education and Character Education learning at SMP Negeri 26 Sorong Regency runs in accordance with the applicable curriculum, namely the Merdeka curriculum for classes VII and VIII and curriculum 13 for class XI. Learning of Islamic Religious Education and Character at the school is carried out as it should by using Islamic Religious Education textbooks for junior high school and equivalent.